2022 Acknowledgements and Reflections - Houran, James (Journal of Scientific Exploration, 2023)
This year brought a whirlwind of learnings, so my warmest thanks to the SSE leadership and JSE editorial team for actively supporting my adjustment to the Editor-in-Chief role. I want to especially acknowledge the production efforts of our stalwart Managing Editor Kathleen Erickson, as well as the selfless and continuing mentorship from the prior editor Stephen Braude. Extremely helpful discussions and guidance also came from colleagues, including Garret Moddel, Julia Mossbridge, Brian Laythe, Mark Rodeghier, Daniel Sheehan, and Michael Sudduth. Their periodic calibrations were much needed and greatly appreciated. Of course, tremendous gratitude goes to the Associate Editors for doing the heavy “thinking and lifting” of evaluating submissions and facilitating quality reviews on a deadline. The time and energy associated with their work can neither be overstated nor overappreciated. This excellent group of scientific advisors likewise challenges me in many ways that enhance my perspective and hopefully my performance—so bravo to Imants Barušs, Jeremy Drake, Álex Escolà-Gascón, Hartmut Grote, Rense Lange, Brian Laythe, James G. Matlock, Julia Mossbridge, Roger Nelson, Mark Rodeghier, Paul Smith, Harald Walach, and N. C. Wickramasinghe.